Women Insurgents, Rebel Organization Structure, and Sustaining the Rebellion: The Case of the Kurdistan Workers' Party. (27th May 2022) - Başer, Çağlayan
Abstract: How do women insurgents affect rebel organizations' structure and survivability? Scholars acknowledge the importance of organization-level dynamics and unit composition for conflict outcomes. However, our understanding of how gender-diverse cadres influence rebel survivability remains limited. I examine the mechanisms through which women sustain armed conflict. I analyze micro-organizational dynamics of rebellion through a qualitative case study of the Kurdish armed movement in Turkey between 1982 and 2015 based on the official archives of the Kurdistan Workers' Party. I show that women insurgents enable tactical diversity, aid the organization's coup-proofing strategy against factions, and mobilize domestic and international audiences. Women contribute most to their organization during crises and due to exploitation of gender inequalities. Analyzing the relationship between gender dynamics, group structure, and evolving rebel strategies, this study shows that the gender composition of the membership is an important factor influencing rebel survivability.